An assessment for the penetration rates of intrusive magmatic rocks by using the direct rotary and percussive drilling methods according to the mineral contents and densities - Kılıç, Ebubekir (My University, 2017)
Abstract Intrusive igneous rocks make up about 95% of the Earth's crust. These rocks are frequently encountered on the foundations of engineering projects such as dams, tunnels, roads, nuclear plants, solid waste repositories, in searching water, mine and oil, and working search and rescue. The aim of this study is the assessment of penetration rates of the granite, diorite, gabbro and peridotite rocks by rotary and percussive drilling methods according to the mineral contents and densities. In this study, the average Mohs hardness, Vicker hardness numbers (VHN) and densities of the rocks obtained by using their primary minerals volumetric rates were used in calculations of penetration rates of intrusive igneous rocks. The highest average Mohs hardness and density values were determined in peridotite, gabbro, diorite and granite rocks, respectively. The highest average Vicker hardness numbers were also determined in peridotite, granite, gabbro and diorite rocks, respectively. It was determined that Vicker hardness numbers increased in rocks with increased quartz and olivine content, so their penetration rates decreased by percussive and rotary drilling methods. The drillability of the rocks was revealed to be inversely proportional to their VHN and densities by both drilling methods. In conclusion, it was determined that the penetration rates of the rocks by both drilling methods were decreased in peridotite, gabbro, diorite and granite, respectively, and penetration rate by percussive drilling method was about 5 times higher than by rotary drilling method. It was assessed that the drilling these rocks by percussive drilling method was more efficient and economical than by rotary drilling method due to the high penetration rate and low risk of drill equipment breaking, when the rocks do not weather. It was also determined that the penetration rate obtained by taking cores from the rocks in rotary drilling was lower than by percussive and uncore rotary drilling methods. Keywords: Density, penetration rate, hardness, igneous rock, percussive drilling, direct rotary drilling.

Magmatik derinlik kayaçları, yerkabuğunun yaklaşık %95'ini oluşturmaktadır. Bu kayaçlara genellikle baraj, tünel, yol, nükleer santral ve katı atık depoları gibi mühendislik projelerinin temelinde, su, maden ve petrol aramalarında ve arama kurtarma çalışmalarında sıklıkla karşılaşılmaktadır. Bu çalışmanın amacı, granit, diyorit, gabro ve peridotit magmatik derinlik kayaçların mineral içeriklerine ve yoğunluklarına göre düz dolaşımlı döner ve darbeli sondaj yöntemleriyle delinebilirlik oranlarının değerlendirilmesidir. Magmatik derinlik kayaçların delinebilirlik oranının hesaplanmasında, kayaçların birincil minerallerinin hacimsel oranları kullanılarak elde edilen ortalama Mohs sertlikleri, Vicker sertlik sayıları ve yoğunlukları kullanıldı. En yüksek ortalama Mohs sertliği ve yoğunluk değerleri sırasıyla peridotit, gabro, diyorit ve granit kayaçlarında belirlendi. En yüksek ortalama Vicker sertlik sayıları da sırasıyla peridotit, granit, gabro ve diyoritte belirlendi. Kuvars ve olivin içeriği artan kayaçların Vicker sertlik sayılarının da arttığı, dolayısıyla darbeli ve döner sondaj yöntemleri ile delinebilirlik oranının azaldığı tespit edildi. Bu kayaçların delinebilirlik oranının, her iki sondaj yönteminde de VHN ve yoğunluk değerleriyle ters orantılı olduğu belirlendi. Sonuç olarak, kayaçların delinebilirlik oranının darbeli ve döner sondaj yöntemlerinde granit, diyorit, gabro ve peridotite doğru düşüş gösterdiği, delinebilirlik oranının ise darbeli sondaj yönteminde döner sondaj yöntemine göre yaklaşık 5 kat daha fazla olduğu saptandı. Delinebilirlik oranının yüksek olması ve delme takımlarının kırılma riski düşük olduğundan dolayı, darbeli sondaj yöntemiyle bu kayaçları delmenin, kayaçlar ayrışmadığı sürece döner sondaj yöntemiyle delmekten daha verimli ve ekonomik olduğu değerlendirildi. Döner sondajda kayaçlardan karot alınarak elde edilen delinebilirlik oranlarının, darbeli ve karotsuz döner sondaj yöntemlerindeki delinebilirlik oranlarından daha düşük olduğu saptandı.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Yoğunluk; Delinebilme oranı; Sertlik; Magmatik derinlik kayaç; Darbeli sondaj; Düz dolaşımlı döner sondaj